Compassionate Learning in Enhancing Anti-Bullying Traits among Students of Pesantren-Based Madrasah Ibtidaiyah - M. Sofyan Alnashr; Abdul Rohman; Ali Imron; Muhammad Jauhari Sofi (UIN Siber Syekh Nurjati Cirebon, 2025)
AbstractThis study aims to analyse the compassionate learning approach to strengthen students' anti-bullying character in pesantren-based madrasahs. The study is conducted at Islamic Elementary School/Madrasah Ibtidaiyah (MI) Tarbiyatul Banin Pekalongan Winong Pati, Indonesia, a pesantren-based madrasah that utilizes a compassionate learning approach. This research employs a qualitative approach using a case study. Data were collected through in-depth interviews with the madrasah principal and teachers, measurement of students' levels of compassion through questionnaires, direct observation, and relevant documentation. Miles and Huberman's interactive data analysis was applied through stages including data collection, data reduction, data presentation, and drawing conclusions. The results indicate that compassion is employed as a learning approach in the madrasah, albeit without a written policy. This approach is reinforced by the madrasah environment that fosters compassion, the integration of compassionate values into learning, and students' empathetic behavior. Compassion-based learning can enhance anti-bullying character traits, as evidenced by 96% of students exhibiting positive empathy, 64% displaying high moral courage, and 84% demonstrating high social awareness. Based on the research findings, schools or madrasahs should develop a design for a compassionate learning environment to bolster students' positive character traits.Keywords: compassionate learning, anti-bullying character, pesantren-based madrasah. AbstrakPenelitian ini bertujuan untuk menganalisis pendekatan pembelajaran berbasis kasih sayang (compassionate learning) dalam memperkuat karakter anti-perundungan pada siswa madrasah ibtidaiyah berbasis pesantren. Studi ini dilakukan di Madrasah Ibtidaiyah (MI) Tarbiyatul Banin Pekalongan Winong Pati, Indonesia, sebuah madrasah yang mengimplementasikan pendekatan pembelajaran berbasis kasih sayang. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Pengumpulan data dilakukan melalui wawancara mendalam dengan kepala madrasah dan guru, pengukuran tingkat kasih sayang siswa melalui kuesioner, observasi langsung, serta dokumentasi relevan. Analisis data dilakukan menggunakan model interaktif Miles dan Huberman yang meliputi tahap pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pembelajaran berbasis kasih sayang telah diterapkan dalam proses pembelajaran di madrasah, meskipun belum tertuang dalam kebijakan tertulis. Pendekatan ini diperkuat oleh lingkungan madrasah yang mendukung nilai-nilai kasih sayang, integrasi nilai-nilai kasih sayang ke dalam pembelajaran, serta perilaku empatik siswa. Pembelajaran berbasis kasih sayang terbukti mampu meningkatkan karakter anti-perundungan pada siswa, yang ditunjukkan dengan 96% siswa memiliki empati yang baik, 64% menunjukkan keberanian moral yang tinggi, dan 84% memiliki kesadaran sosial yang tinggi. Berdasarkan temuan ini, sekolah atau madrasah disarankan untuk merancang lingkungan pembelajaran yang berlandaskan kasih sayang guna membentuk karakter positif pada siswa.Keywords: pembelajaran berbasis kasih sayang, karakter anti-perundungan, madrasah berbasis pesantren.